Storyworlds: journey into the earth - Edmonds, William; McPhillips, Robert McNicholas, Shelagh (Heinemann UK, 1997)
"Journey into the Earth" takes readers on an adventurous exploration beneath the Earth's surface, where they discover fascinating underground landscapes, minerals, and creatures. The story blends science and adventure, encouraging curiosity about the planet's inner workings.